Does habitat loss affect tropical myxomycetes? - Rojas Alvarado, Carlos Alonso (2014)
The effect of habitat loss on the dynamics of myxomycete assemblages has been poorly studied thus far. For this reason, a premontane moist forest surrounded by human-created pastures on the Caribbean slope of Costa Rica was selected to carry out a pilot ecological evaluation using a systematic approach. In the area of study, a series of forest zones representing a gradual continuum of habitat variation was selected and characterized using structural forest parameters. Fruiting bodies of myxomycetes were surveyed across these zones and microhabitat variables were measured when fruiting bodies were found. Results indicated that species richness, species diversity and the number of unique species recorded as fruiting bodies increased linearly from areas without suitable habitat to areas with complete suitable habitats and such pattern was shown to be correlated with canopy openness. Since the latter factor is clearly dissimilar across areas with structural differences in the forest being studied, the results presented herein suggest that myxomycetes are affected by the modification and loss of suitable habitats